prove that ( 1-sinA + cosA)^2 = 2(1+cosA) (1-sinA)​

Question

prove that ( 1-sinA + cosA)^2 = 2(1+cosA) (1-sinA)​

in progress 0
Kaylee 1 month 2021-08-12T17:13:01+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-08-12T17:14:18+00:00

    Answer:

    I assume that the angle a should be A. Then we wish to prove that

    (1-sinA-cosA)^2=2(1-sinA)(1-cosA).

    (1-sinA-cosA)^2=1–2(sinA+cosa)+(sina+cosA)^2=

    1–2(sinA+cosA)+sinA^2+cosA^2+2(sinA*cosA)=

    2(1-sinA-cosA+sinA*cosA)=2(1-sinA)(1-cosA).

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )